Ecological panels as an alternative for waste from mechanical processing of Amazonian species - Marques, Marcos; Nascimento, Claudete Catanhede do; Araujo, Roberto Daniel de (International Journal for Innovation Education and Research, 2020)
The wood residues resulting from the operational phases in companies in the forestry market are normally considered by-products and, therefore, are discarded or reused for energy production, however, this material has a greater potential, such as the generation of new products through agglutination, which may generate a new segment in the wood industry, causing competition between products of native and planted species. This research aimed to develop agglomerated panels using residues of two tree species from the Amazon (Dinizia excelsa Ducke and Manilkara huberi (Ducke) Chevalier) and a mixture of commercial Amazonian species of high density, with the purpose of greater added value and a possible solution to reduce the negative environmental impacts of carbon emissions. The experimental design consisted of three treatments with five repetitions in each. Experimental panels were produced with a nominal density of 0.80 g/cm³, using castor oil-based resin with 10% percentages. The panels were pressed with a pressure of 10 MPa, temperature of 100ºC and with a pressing time of 10 minutes. The evaluations of the results obtained were compared with the ANSI A208.1 / 2009 standard and with the literature on agglomerated panels of tropical species. In physical properties, the panels showed compliance with the values found in the literature, however, they are outside the standard of the norm. Regarding the mechanical properties, the MOR values classify the panels in the medium to high density standard in accordance with the standard. The results of the MOE are superior to those of the existing literature, with emphasis on the perpendicular traction that presents values consistent with the literature. The machining evaluations carried out according to ASTM D 1666-11 / 2011, show a good quality in the finish. In general analysis and in compliance with the regulations, all panels have economic viability and potential for industrialization.